Implementation of Inventory Accounting for Spareparts in Accordance with PSAK No. 202: Case Study of PT. Bosowa Berlian Motor Manado - Siti Sarah Bactiar; Opa Mustopa; Lidya A. Maramis (STIE Amkop Makassar, 2026)
This study aims to analyze the suitability of the application of spare parts inventory accounting at PT Bosowa Berlian Motor Manado with PSAK No. 202 regarding inventory. The research uses a descriptive qualitative approach with data collection techniques in the form of observations, interviews, and documentation to obtain an in-depth picture of the practices that occur in the field. The results of the study show that the company has implemented a perpetual inventory recording system and uses the FIFO (First In, First Out) method in inventory assessment, which has generally referred to PSAK No. 202. In terms of presentation and disclosure, inventory is recorded as part of current assets in the financial statements and is recognized as a cost of goods sold in the income statement. However, in the measurement aspect, weaknesses are still found, namely the recognition of all costs related to the acquisition of inventory, so that the value presented does not fully reflect the acquisition cost in accordance with applicable standards. Based on these results, it can be concluded that the implementation of inventory accounting at PT Bosowa Berlian Motor Manado in general is in accordance with PSAK No. 202, but there is still a need for improvements, especially in the measurement aspect so that cost recognition can be carried out more appropriately.